Abbasid Caliphate: Essential Features and Town Planning - Maria Ansari; Shumaila Qureshi; Farjad Faiz, (Dialogue Social Science Review (DSSR), 2025)
The current article is the exploration of the key elements of the town planning of Abbasid dynasty and aims to show the Golden Period of Islamic architecture. During the time period of Abbasid dynasty their Caliphs especially al-Mansur and Haroon-ur-Rasheed played a vital role in the town planning of this area. It was the time of highly developed forms of Islamic art and Architecture. The culture mix of the Persians and Arabs caused a rise in Islamic advances in sciences, art and architecture. Present paper is focusing on the important elements of town planning of Abbasids reflecting the great aesthetic sense and innovative ideas of its builders. For the purpose to describe the essential features of their well-planned towns the most famous Round City of Baghdad which was the cluster of some other cities has been taken mainly in to the consideration. Key Words: Town planning, Abbasid dynasty, Baghdad